Equal division, efficiency, and the sovereign supply of labor - Kranich, Laurence (American Economic Review, 1994)
The canonical problem of equity in production economies consists of two agents with different tastes and abilities, each of whom contributes labor to produce a single consumption good. As a criterion for distributive justice, the author requires that if both agents work equal numbers of hours, they should divide the output equally. He also requires that the labor-supply decision should remain sovereign. Sufficient conditions are established for achieving an efficient allocation using a division procedure that is consistent with the equal-division-for-equal-work principle and it is shown that the conditions are satisfied in many standard economies. Copyright 1994 by American Economic Association.